The state of the European Union - Cowles, Maria Green (Oxford University Press, 1995)
With contributions from leading scholars, this book examines the European Union in a theoretically informed, empirically grounded manner. The book begins by exploring the evolving nature of the European polity and its capacity for change. This is the fifth volume in the biannual series State of the European Union produced under the auspices of the American European Community Studies Association